Aspects of venous ulcer prevention, an integrative review (Research, Society and Development, 2022)
Objective: to review the theoretical bases, the evidence on invasive and non-invasive preventive measures, as well as the treatment methods for venous ulcers. Methodology: this is an integrative literature review study. The following databases were used: Scientific Electronic Library Online (SciELO), PubMed, EBSCO Journal Portal and Google Scholar. Publications in Portuguese, English, Spanish and German were selected. Results: the final sample consists of 11 articles and 1 book, published between 2017 and 2022, but books published before the stipulated date for the research were used, as it is a consolidated reference. The most relevant results of each of the articles and books were analyzed, as well as: authors' name, article title, sample size, method used, database, year of publication and objective. Among these, 6 are from Brazil, 2 from the USA, 1 from Canada, 1 Mexico and 1 from Croatia. Conclusion: from the analysis of the articles collected, few articles were noted detailing prevention, as well as the lack of knowledge of professionals regarding ways to prevent. In addition, it is noticed that patients do not carry out treatments due to the lack of importance to the diagnosed disease.